Perceptions of intermediate students towards nursing as a career choice in Swat Khyber Pakhtunkhwa - Sultan, Amir; Bibi, Afrooz; Jamal, Haseen; Ahmed, Fayaz; Shabana; Imran, Muhammad (Journal of the Pakistan Medical Association, 2023)
The study aimed to explore the views of intermediate students toward nursing as a career of choice. A cross-sectional design was used for the study conducted between June and July 2022, in two public colleges in district Swat Khyber Pakhtunkhwa. The sample size of the study was 146, obtained through random sampling using a self-administrated questionnaire on a 3-point Likert scale. Previous studies show that (61%) agreed, (19%) were neutral, and (20%) disagreed for selecting nursing as a career. Eighty-two (56%) students in the current study agreed, 47 (32%) disagreed, and 17 (12%) were neutral when asked if they planned to enrol in nursing school. The study noted that intermediate students in district Swat have a positive attitude towards nursing as a result of the establishment of multiple nursing colleges and the opportunity to work as a nurse in government hospitals or as a nurse educator.